GREEN MARKETING TO SATISFY BUYER’S DEMANDS AND SUSTAINABLE DEVELOPMENT: CHALLENGES AND PROSPECTS - Singh , Krishanveer (International Journal of Psychosocial Rehabilitation, 2020)
Green Marketing has evolved special implications within the trendy market. Green shows purity by means of way of exceptional, fair price and worth in dealings. Green advertising and marketing awareness to plug green products to fulfill the wants and needs of purchasers. It implements revolutionary techniques of product variation, lively product techniques, maintaining sustainability and various approaches of marketing etc. The vision of Green advertising is doing enterprise alongside defensive ecological environment. Present day customers want to be socially responsible by using consciously operating for the reason for environmental protection. The commercial enterprise supported current developments have created global strain upon employers to be environmental pleasant. Now, more groups intention to provide client and Industrial Goods that are less hazardous to the surroundings. Every organization eventually shifting towards becoming inexperienced to revelin the primary mover advantages offered by means of regulating bodies. Green Marketing guarantees cease of the day sustainability and profitability. it's multi beneficial with reduced cost, encourage accessibility to new markets with aggressive advantage, growth mo- rale of worker for being a place of environmental cause, satisfies the consumer with fitness ser- vices and products. This paper is descriptive in nature and thus the data are accrued from secondary assets like, text books, journal publications, enterprise reviews and websites. This paper analyses the results of green advertising in the Indian enterprise situation by means of reading exclusive Green Business organizations listed within the Go Green Directory